Use of Continuous Glucose Monitoring in Non-ICU Hospital Settings for People With Diabetes: A Scoping Review of Emerging Benefits and Issues. (March 2023) - Clubbs Coldron, Benjamin; Coates, Vivien; Khamis, Amjed; MacRury, Sandra
Background: Evidence indicates that poor glycemic control is associated with increased morbidity and length of stay in hospital. There are a wide range of guidelines published, which seek to ensure safe and effective inpatient glycemic control in the hospital setting. However, the implementation of these protocols is limited in practice. In particular, the feasibility of "flash" and continuous glucose monitoring (CGM) remains untested on general wards. Method: Scoping Review. Results: If used in the general ward hospital settings, CGM and flash glucose monitoring (FGM) systems could lead to improved glycemic control, decreased length of stay, and reduced risk of severe hypoglycemia or hyperglycemia. Potential problems include lack of experience with this technology and costs of sensors. Rapid analysis of glucose measurements can facilitate clinical decision making and therapy adjustment in the hospital setting. In addition, people with diabetes may be empowered to better self-manage their condition in hospital as they have direct access to their glucose data. Conclusions: More studies are required in which the feasibility, benefits and limitations of FGM and CGM in non–intensive care unit hospital settings are elucidated. We need evidence on which types of hospital wards might benefit from the introduction of this technology and the contexts in which they are less useful. We also need to identify the types of people who are most likely to find FGM and CGM useful for self-management and for which populations they have the most benefit in terms of clinical outcomes and length of stay.